The importance of intensive chemotherapy for advanced Hodgkin lymphoma in children - E.S. Belyaeva; N.A. Susuleva; T.T. Valiev (LCC «Medicine-Inform», 2020)
The importance of intensive chemotherapy for advanced Hodgkin lymphoma in children E.S. Belyaeva1, N.A. Susuleva1,2, T.T. Valiev1,2 1Scientific Research Center of Pediatric Oncology and Hematology of the N.N. Blokhin National Medical Research Center of Oncology, Moscow, Russian Federation 2Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation Background: currently, Hodgkin lymphoma (HL) in children is characterized by excellent treatment outcomes due to the use of modern risk-adapted treatment strategies. Overall survival rate for HL is more than 90%, therefore, further development of therapeutic protocols should be focused on minimizing toxicity and late adverse reactions. Aim: to improve HL treatment outcomes in children by intensive risk-adapted chemotherapy and personalized approach to radiotherapy. Patients and Methods: 134 children with HL stage II (with large tumor mass) to IV diagnosed for the first time were enrolled in the study. Morphological immunological verification of the diagnosis was performed in all children. HL was staged using imaging techniques (i.e., gallium-67 or technetium-99 imaging, computed tomography, positron-emission tomography). HL-2007 SRC POH protocol based on escBEACOPP regimen was applied. To assess treatment efficacy, overall, relapse-free, and event-free survival rates w ere calculated. Statistical analysis was performed using SPSS19.0 software. Results: risk-adapted treatment based on the terms of complete remission achievement has provided high survival rates even in advanced HL stages. Thus, 14-year overall survival rate was 97.7±1.3%, relapse-free survival rate 92.2±2.4%, and event-free survival rate 90.7±2.6%. Among late adverse reactions, secondary tumors (i.e., breast cancer after mediastinal radiotherapy) were reported. In girls with early (after 4 chemotherapy courses) complete response, we were able to avoid radiotherapy which was not associated with poorer treatment outcomes (overall survival rate was 98.5±1.5%). Conclusion: personalized HL treatment using HL-2007 SRC POH regimen provides high survival rate in most children and the avoidance of radiotherapy in girls with early complete response without negative impact on treatment outcomes. Our findings demonstrate that this therapeutic regimen can be recommended for c hildren with advanced HL and large tumor mass at baseline. Keywords: Hodgkin lymphoma, chemotherapy, radiotherapy, children, survival. For citation: Belyaeva E.S., Susuleva N.A., Valiev T.T. The importance of intensive chemotherapy for advanced Hodgkin lymphoma in children. Russian Journal of Woman and Child Health. 2020;3(2):149-154. DOI: 10.32364/2618-8430-2020-3-2-149-154.